Ideological shift in interpreted parliamentary speeches: The conference interpreter as meaning co-constructor - Dobkiewicz, Patryk (Studia Anglica Posnaniensia, 2023)
Studies of interpreted political discourses in multiple contexts and language combinations have shown interpreters mitigating or intensifying ideologically loaded source texts. This article employs methods of the Discourse-Historical Approach to analyse ideological shifts between source texts and target texts across the left-right political spectrum. Qualitative analysis of a set of Englishlanguage European Parliament speeches and their interpretations into Polish identifies a variety of linguistic means through which the ideological load of source text references to political actors and phenomena may be weakened or strengthened. The results of a quantitative analysis point towards verb phrases being more susceptible to ideological shift than noun phrases, while the relationship between ideological shift and political orientation of the speaker requires further study. This paper contributes to the growing body of research highlighting the ideological and discourse-constructive potential of interpreters.